MG-121 Complexity of phenotypes of females with unbalanced x-autosomal translocations exemplified by a case with 46, x, der (x)t (x;16)(p11.2;p13.2) karyotype. (4th December 2015) - Grafodatskaya, Daria; Dell, Edith; Li, Chumei; McCready, Elizabeth
Abstract : Background: Females with unbalanced X-autosomal translocations frequently exhibit skewed X-chromosome inactivation, as cells with the least functional imbalance have selective advantage. However, predicting the inactivation status of the translocated autosomal segment and its impact on phenotype is challenging. Active vs inactive state can depend on translocation breakpoint and sequence features of the translocated segment. Objective: Report a case with 46, X, der (X)t (X;16)(p11.2;p13.2) karyotype and discuss karyotype/phenotype correlations. Results: We report a 18 month old girl with intrauterine growth restriction, failure to thrive, cardiac anomalies and dysmorphic features. Oligonucleotide microarray has revealed a terminal ~9 Mb gain of chromosome 16p and terminal loss of most of Xp. A de novo unbalanced translocation t (X;16)(p11.2;p13.2) was confirmed by karyotype analysis and family studies. Androgen receptor assay further showed complete skewing of X-inactivation, suggesting that derivative X-chromosome was inactive. Phenotype of our patient was not fully consistent with either Xp deletion or 16p13.3 duplication, leaving a question about inactivation status of the translocated 16p material. A case with 46, X, der (X) t (X;16)(q28;p12) karyotype and phenotype consistent with 16p13.3 duplication syndrome was previously reported. Replication studies have shown skewed inactivation of the der (X), not spreading into 16p translocated segment. 1 Conclusions: Our patient phenotype suggests that while Androgen Receptor assay provides valuable information in regard of X-inactivation skewing, it has limitations for karyotype/phenotype correlations for patients with unbalanced X-autosomal translocation. Additional analysis of inactivation status of the genes of the translocated segment is underway to understand the phenotype of our patient. Reference: Preis W, Barbi G, Liptay S, Kennerknecht I, Schwemmle S, Pohlandt F. X/autosome translocation in three generations ascertained through an infant with trisomy 16p due to failure of spreading of X-inactivation. Am J Med Genet . 1996;61 (2):117–21